Sindrom cri du chat - prikaz primera - Besednjak-Kocijančič, Lilijana (Zdravniški vestnik, 2001)
Background. The article describes a patient with clinical features of the Cri du chat syndrome. The syndrome is relatively rare chromosomal disorder caused by a deletion of the tip of the short arm of chromosome 5. Cry that sounds like the meowing of a cat, typical facial dysmorphism, primordial growth deficiency and severe psychomotor retardation with microcephaly and hypotonia are the hallmark clinical features. Severity of the phenotype is associated with the extend of the deletion, so FISH is indicated. A level of developmental delay strongly correlates also with early special schooling and supportive home environment. Conclusions. The presented boy lives at home but he daily attends social, verbal and motorical education in a medical institute. In eleven months of schooling a big progress in psychomotor development was achieved.
Keywords: Child, preschool; Chromosome deletion; Chromosomes, human, pair 5; Cri-du-chat syndrome; Delecija kromosoma; Fenotip; Kromosomi človeški 4-5; kromosomske anomalije; Mačji krik, sindrom; Otrok predšolski; Phenotype; sindrom cri di chat